An initial examination of the psychometric properties of the Diagnostic Instrument for Social and Communication Disorders (DISCO-11) in a clinical sample of children with a diagnosis of Autism spectrum disorder. (26th September 2022) - Anglim, Margo; Conway, Emma Victoria; Barry, Myra; Kashif, Muhammad; Ackermann, Pauline; Moran, Aoife; O'Connell, Anne Sophie; Guerin, Suzanne
Abstract : Introduction: The diagnostic interview for social and communication disorders (DISCO – 11; Wing 2006), is a semi-structured, interview-based instrument used in the diagnosis of children with autism spectrum disorder (ASD). This paper explores the psychometric properties of the DISCO-11 used in a specialist Paediatric clinical setting. Two key research questions were examined; (1) Does the factor structure of the DISCO-11 reflect the diagnostic and statistical manual 5th edition (DSM-5, American Psychiatric Association [APA], 2013) dyad of impairment in ASD? (2) Is there evidence of diagnostic stability over time using the DISCO? Methods: Review assessments of 65 children with ASD were carried out using standardised measures including the DISCO-11 and the autism diagnostic observation schedule. Results: The results revealed two factors resembling the DSM-5 algorithms, as used in DISCO-11, which were named as social-communication, and restricted and repetitive behaviours. The reliability, for the overall DISCO score was good (Cronbach's alpha = 0.78). The social communication and social interaction subscale showed good reliability (Cronbach's Alpha = 0.77) as did the restricted and repetitive patterns of behaviour, interests or activities subscale (Cronbach's Alpha = 0.74). Acceptable internal reliability was found for the overall DISCO score and the subscales of social communication and social interaction and the restricted and repetitive patterns of behaviour, interests or activities. Test–retest showed good stability of diagnosis over time. Discussion: This study supports that the DISCO-11 shows potential as a valid and reliable instrument that can be used both for clinical and research purposes.